The control of postharvest ripening processes and its implications for the productivity of mango processing - Sybille Neidhart (2018)
© 2007, Springer-Verlag Berlin Heidelberg. The production of high-quality food depends not only on an appropriate processing technology but also on the selection of proper raw materials. This experience, well known among food manufacturers, can be exemplified in the case of mango processing.